2016
DOI: 10.1016/j.amjmed.2015.05.038
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone Applications for Patients' Health and Fitness

Abstract: Healthcare providers are often looking for ways to objectively monitor and improve their patients' health and fitness, especially in between patient visits. Some insurance companies are using applications data as incentives to improve health and lower premiums. As more and more people start to use smartphones, they may provide a tool to help improve a patient's health and fitness. Specifically, fitness applications or "apps" on smartphones are programs that use data collected from a smartphone's inbuilt tools,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
199
1
16

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 325 publications
(218 citation statements)
references
References 34 publications
2
199
1
16
Order By: Relevance
“…Cellnovo has developed an insulin pump approved for use in the United Kingdom and France that incorporates a 3-axis accelerometer capable of monitoring physical activity. 52,56 With the computational power enabling both integration of data and high-level analysis now available in smartphones, there has been great interest in using these as an intelligent hub 57,58 for the integration of physiological signals in CLC. [59][60][61][62][63][64] Furthermore, cloud-based data systems enable the health care team to access and analyze CGM, CSII, and CLC data.…”
Section: Future Technologies Patient Factors and Prospects For Futumentioning
confidence: 99%
“…Cellnovo has developed an insulin pump approved for use in the United Kingdom and France that incorporates a 3-axis accelerometer capable of monitoring physical activity. 52,56 With the computational power enabling both integration of data and high-level analysis now available in smartphones, there has been great interest in using these as an intelligent hub 57,58 for the integration of physiological signals in CLC. [59][60][61][62][63][64] Furthermore, cloud-based data systems enable the health care team to access and analyze CGM, CSII, and CLC data.…”
Section: Future Technologies Patient Factors and Prospects For Futumentioning
confidence: 99%
“…An apps inventory by Higgins 11 and Knight et al, 12 found a typical fitness App to be more effective when behaviour change techniques are incorporated, though very few of the apps included this element in the design. Social networking, pairing with health device and additional health parameters were some of the common technological features.…”
Section: Physical Activitymentioning
confidence: 99%
“…With such monitors and trackers, behavioural changes that improve eating habits and physical activity levels have been observed in young adults. Thus such monitoring apps do encourage patients to be more aware of their daily condition (Higgins 2015).…”
Section: Patient Data Management [Table 2]mentioning
confidence: 99%